Two-Year Outcomes after Left Main Coronary Artery Percutaneous Coronary Intervention in Patients Presenting with Acute Coronary Syndrome - Jia, Si-Da (J Interv Cardiol, 2020)
OBJECTIVES: We aim to evaluate long-term outcomes after left main coronary artery (LMCA) percutaneous coronary intervention (PCI) in patients presenting with acute coronary syndrome (ACS). BACKGROUND: PCI of the LMCA has been an acceptable revascularization strategy in stable coronary artery disease. However, limited studies on long-term clinical outcomes of LMCA PCI in ACS patients are available. METHODS: A total of 6429 consecutive patients with ACS undergoing PCI in Fuwai Hospital in 2013 were enrolled. Patients are divided into LMCA group and Non-LMCA group according to whether the target lesion was located in LMCA. Prognosis impact on 2-year major adverse cardiovascular and cerebrovascular events (MACCE) is analyzed. RESULTS: 155 (2.4%) patients had target lesion in LMCA, while 6274 (97.6%) patients belong to the non-LMCA group. Compared with non-LMCA patients, LMCA patients have generally more comorbidities and worse baseline conditions. Two-year follow-up reveals that LMCA patients have significantly higher rate of cardiac death (2.6% vs. 0.7%, p = 0.034), myocardial infarction (7.1% vs. 1.8%, p < 0.001), in-stent thrombosis (4.5% vs. 0.8%, p < 0.001), and stroke (7.1% vs. 6.4%, p = 0.025). After adjusting for confounding factors, LMCA remains independently associated with higher 2-year myocardial infarction rate (HR = 2.585, 95% CI = 1.243–5.347, p = 0.011). CONCLUSION: LMCA-targeted PCI is an independent risk factor for 2-year myocardial infarction in ACS patients.